Liderazgo y clima laboral en los servidores de la Institución Educativa Inicial Primaria Secundaria Manuel Enrique Rojas Vela Contamana 2024 - Zuta Paredes, Herths Akira (2025)
In this final report, the objective was to determine the relationship between leadership and work environment in the employees of the Manuel Enrique Rojas Vela Initial Primary Secondary Educational Institution of Contamana 2024. It was developed under an applied approach of descriptive-correlational level and non-experimental design. Which was composed of a population of 84 employees to whom a survey was applied to collect information and data. The results show that leadership received an adequate rating by 36% of those surveyed. This assessment is due to the fact that the institution's employees indicated that consensus on tasks is sometimes facilitated by the leader and that, sometimes, agreements are established based on tasks. However, they indicated that the leader almost always establishes objectives considering the opinions of the employees. On the other hand, the work environment in the institution was also rated as adequate with 36%. The participants stated that, in most cases, their opinions are considered and well received by their coworkers. However, it was observed that only occasionally the members of the work group are close to each other. Finally, a moderate and positive correlation was found between leadership and work environment, with a correlation coefficient of 0.573. This suggests that as leadership improves, work environment tends to improve as well. Furthermore, the statistical significance value (p-value) was 0.000, which is less than 0.01, indicating that the correlation is statistically significant at the 1% level of bilateral significance.